Involvement of growth differentiation factor 15 in paradoxical relationship between body mass index and mortality in patients with suspected or known coronary artery disease; The ANOX Study. (3rd October 2022) - Matsuda, M; Suzuki, M; Ajiro, Y; Shinozaki, T; Sakagami, S; Yonezawa, K; Shimizu, M; Funada, J; Takenaka, T; Morita, Y; Iguchi, M; Abe, M; et al.
Abstract: Background: Obesity is a well-established risk factor for type 2 diabetes mellitus, hypertension and dyslipidemia, leading to coronary artery disease (CAD). Nevertheless, body mass index (BMI) is inversely associated with cardiovascular (CV) mortality in patients with cardiac disorders, termed "obesity paradox". However, the underlying mechanism remains unclear. Purpose: To clarify important factors involved in the pathogenesis of obesity paradox. Methods: Using data from a multicenter, prospective cohort of 2, 418 patients with suspected or known CAD enrolled in the ANOX study, we assessed the relationship between BMI at baseline and the incidence of CV death over 3 years, and investigated the involvement of several endocrine factors which were previously reported to have some roles in obesity and heart diseases, such as adiponectin, N-terminal pro-brain natriuretic peptide (NT-proBNP) and growth differentiation factor 15 (GDF-15), in the relationship between BMI and CV death. Results: In Kaplan-Meier analyses, the lower quartiles of BMI and the higher quartiles of adiponectin levels were paradoxically associated with the higher cumulative incidence of CV death. To clarify the important factors involved in the paradoxical association between BMI or adiponectin and mortality, we first investigated independent determinants for BMI and adiponectin levels respectively, using multiple stepwise regression analyses among many clinical factors, and then narrow down the prognostic factors commonly associated with BMI and adiponectin, which were age, hemoglobin and NT-proBNP. Interestingly, circulating levels of GDF15 were significantly correlated with NT-proBNP levels, and the presence of anemia raised the gradient of the correlation line in a scatter plot (without anemia, r=0.139, p<0.0001; with anemia, r=0.228, p<0.0001). Moreover, the highest GDF15 quartile showed significantly lower BMI and higher adiponectin levels compared to the lower quartiles (p<0.001 and p<0.001, respectively, by Student t-test). In Cox proportional hazard models, hazard ratios (HRs) of BMI (per 1-unit increase) were 0.90 (95% confidence interval [CI], 0.85–0.96) for CV death. Additional adjustment for hemoglobin, NT-proBNP, adiponectin or GDF15 diminished the statistical significance (HR, 0.92 [95% CI, 0.87–0.99], 0.95 [0.89–1.01], 0.92 [0.87–0.99], or 0.93 [0.87–0.99], respectively). Conclusions: The lower BMI and the higher adiponectin levels were paradoxically associated with the higher incidence of CV death in patients with CAD. This paradox may be mediated by cardiac endocrine factors induced by cardiac stresses, including GDF-15 in addition to natriuretic peptides. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): The ANOX study is supported by a Grant-in-Aid for Clinical Research from the National Hospital Organization.